Interactional justice: the role of emotions in the performance of loyalty - Flower, Lisa (Routledge studies in the sociology of emotions, 2020)
Lawyers and Loyalty -- Legal Systems and Loyalty -- The Emotional Courtroom -- Loyalty and Disloyalty -- The Facework of Defence Lawyers -- The Emotion Work of Defence Lawyers -- The Teamwork of a Criminal Trial.